A qualitative study exploring why adults with intellectual disabilities and obesity want to lose weight and views of their carers. Issue 1 (December 2015) - Jones, N.; Melville, C.; Harris, L.; Bleazard, L.; Hankey, C.
Abstract Background Obesity is more prevalent in adults with intellectual disabilities (ID) compared to the general population. Motivations for weight loss may influence engagement with weight management programmes and have only been studied in adults without ID. Aims: To determine reasons given by adults with ID and obesity for seeking weight loss and whether these reasons differ from those of their carers. Methods Prior to a multi-component weight management intervention, participants were asked "why do you want to lose weight?" Carers were asked their views and these were compared to the answers given by the adult with ID. Responses were themed. The Fisher's Exact analysis was used to test for any relationship between reasons for seeking weight loss and participants' level of ID, age, gender and BMI. Results Eighteen men and 32 women; age 41.6 SD 14.6 years; BMI 40.8 SD 7.5 kg/m2 ; Level ID Mild (28 %), Moderate (42 %), Severe (22 %), Profound (8 %). Eleven were unable to respond. Six themes emerged; Health; Fitness / Activity / Mobility; Appearance / Clothes; Emotional / Happiness; For Others; Miscellaneous. The most frequent reason given overall and by women was "appearance." Carers cited "health" most frequently and "appearance" least, rarely agreeing with participants. "Health" was given as a reason more from older adults and those with milder ID. No statistically significant associations were found between reasons for seeking weight loss and BMI age, gender or level of ID but the differing views of adults with ID and their carers were clear. Conclusions Views of adults with obesity and mild or moderate ID can be collected. The opposing views of adults and their carers may affect motivation for weight loss.